REAKING INTO THE WORLD THROUGH INSTAGRAM: THE SECRET TO ERIGO’S SUCCESS IN THE GLOBAL MARKET - Haeriyah, Yayah; Mulyana, Ahmad (Universitas Mercu Buana, 2025)
Erigo’s participation in New York Fashion Week was a strategic move to enhance the international profile of Indonesian fashion products. The event attracted significant attention on social media, particularly Instagram, and leveraged Indonesian consumers’ interest in internationally associated products. A sense of pride, along with increased brand awareness and positive domestic brand perception, emerged from Erigo’s participation. Erigo successfully demonstrated that an active presence on social media—especially Instagram—is essential for increasing brand awareness, enhancing customer engagement, and boosting sales. Using a qualitative case study method involving observation, interviews, and documentation, this research aims to analyze Erigo’s marketing strategies in improving brand awareness in Indonesia. The findings indicate that Erigo implemented consistent, integrated, and audience-focused communication by combining Integrated Marketing Communication (IMC) strategies with the AISAS approach.